Pengaruh Neraca Anggaran terbadap Neraca Perdagangan Bilateral Indonesia dengan 87 Negara Mitra Dagangnya 2004-2008 : Studi Data Panel - AGUSTIN, GRISVIA (Jurusan Ekonomi Pembangunan Fakultns Ekonomi Universitas Negeri Malang (FE UM), 2011)
Export-Import activities bilaterally between Indonesia and its partner can influence economic 'bath Those export-import activities are noted in bilateral balance of trade. It is requited to observe condition of export and impost in bilateral balance of trade among Indonesia , partner that regarded to balance of tea and government expenditure as balance of budget comperration among Indonesia's balance of tat-government expenditure and its partner • ua-govenunem expenditure, balance). According to result of regression model, variable Z 'widget, significantly have negative influence to variable Y. Since Indonesia's balance of where government expenditure is greater than tar), it will constrain Indonesia's s ewe surplus of Indonesia's bilateral balance of trade or increase deficit of balance of trade.